Temperature-dependent raman and dielectric spectroscopy of BiFeO3 nanoparticles: signatures of spin-phonon and magnetoelectric coupling - Jaiswal, Adhish; Das, Raja; Maity, Tuhin; Vivekanand, K.; Adyanthaya, Suguna D.; Poddar, Pankaj (Journal of Physical Chemistry C, 2010)
We report the temperature-dependent Raman and dielectric spectroscopy of chemically synthesized BiFeO3 nanoparticles (average size similar to 50-60 nm). The Raman spectra (90-700 K) show two sets of transitions in the lowest Raman E mode, associated with Bi-O bond motion situated in close proximity to the spin reorientation transitions reported for BiFeO3, thereby indicating the existence of possible coupling between magnons and phonons for particle size below the helical order parameter (62 nm). These transitions are slightly shifted in temperature in comparison to the bulk single crystals. We also observe a step-like behavior in Raman peak position around the Neel temperature, suggesting that the phonons are influenced by the magnetic ordering in nanosized BiFeO3. The heat-flow measurements show two sharp endothermic peaks at 1094 and 1223 K representing rhombohedral to orthorhombic or monoclinic transition followed by transition into the cubic phase above 1200K. The low temperature (20-325 K), frequency-dependent (1-10(6) Hz) dielectric constant and loss tangent measurements show that the loss tangent (similar to 10(-3)) and ac conductivity values (similar to 10(-8) Ohm(-1)-cm(-1)) are orders of magnitude lower than the reported values for BiFeO3 ceramics, indicating high levels of ionic purity of our samples. The real part of the permittivity shows a slight reduction in its value (similar to 30) in comparison to the bulk single crystals. Similar to the Stokes Raman shift, its temperature-dependent dielectric constant also shows four weak anomalies at similar to 85, 168, 205, and 230 K situated in close proximity to the spin reorientation transitions, indicating magnetoelectric coupling.

Tunable band gap and coercivity of bismuth ferrite-polyaniline core-shell nanoparticles: the role of shell thickness - Chaturvedi, Smita; Das, Raja; Poddar, Pankaj; Kulkarni, Sulabha (RSC Advances, 2015)
We report a tunable band gap of bismuth ferrite-polyaniline core-shell nanoparticles from 2.24 to 1.98 eV and the variation of coercivity from 118 to 100 Oe, by varying the thickness of the polyaniline shell. Bismuth ferrite nanoparticles were synthesized via a chemical route and coating of polyaniline was achieved by a double surfactant layer technique. Coating of polyaniline introduced oxygen vacancies, local distortions and microstrains in the bismuth ferrite lattice which resulted in a change in the Fe-O-Fe bond angle of the bismuth ferrite lattice. This is confirmed with structural analysis tools i.e. X-ray Diffraction, Fourier Transform Infrared Spectroscopy and Raman spectroscopy. Moreover, the absorption of light around 600 nm is increased and photoluminescence emission around 430 nm is decreased, as the thickness of shell is increased, which also indicates the changes in optical properties due to variation in shell thickness. Thus tunability of the band gap and coercivity is achieved as a function of shell thickness in bismuth ferrite-polyaniline core-shell nanoparticles.